EKSPLORASI ETNOMATEMATIKA DALAM AL-QUR’AN SEBAGAI SUMBER BELAJAR - Atmadi; Nuryami (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2024)
Mathematics is one of the subject areas taught from elementary school to high school and even to universities. Mathematics is also one of the subjects that is considered difficult by many students, but mathematics is very important in improving human thinking and this science also plays a very important role in everyday life. Through this ethnomathematics exploration, students will find it easier and more enjoyable to learn mathematics from the Qur’an. Mathematics has a close relationship with the Qur’an without us realizing it, such as odd numbers, even numbers, and prime numbers listed in surah Al-kahf verse 22, verse 25, Al-ankabut verse 14, Al-baqarah verse 261, and annisa’ verse 11-12. The purpose of this research is to describe and elaborate mathematics learning in number theory contained in the Qur’an. The method in this research is using qualitative method which is done by observation and literature study. From this research, it is known that there is a relationship between the words of God contained in the Qur’an and the concept of mathematics, and it is proven that always math lessons can solve all problems in Islam. This research is expected to facilitate the learning of mathematics and can show that there is a connection with the Qur’an. Thus later mathematics lessons are not only as ordinary subjects, but can also be seen in religion, so the researcher took the title Exploration of Ethnomathematics in the Qur’an as a learning resource.Keywords: exploration, ethnomathematics, Qur’an